Perspectives on Current Mechanical Ventilation Use and Training in Pediatric Critical Care Medicine Fellowship Programs in the United States - Malone, Matthew P.; Bennett, Erin; Irby, Olivia Katherine; Pasala, Sanjiv; Sanders, Ronald C., Jr.; Spray, Beverly J.; Dalabih, Abdallah (Journal of Pediatric Intensive Care, 2022)
Mechanical ventilation (MV) is an integral part of the care of the critically ill child, and contemporary MV includes a myriad of sophisticated modalities that should be tailored to specific disease pathology and severity. This requires Pediatric Critical Care Medicine (PCCM) physicians to have comprehensive training and experience with various modes. We sought to assess and describe the current landscape of MV practices and training from PCCM fellowship programs. To describe current MV practices and training in PCCM fellowship programs and assess the different modes of MV to which trainees are exposed, a piloted survey was sent to all 67 American PCCM fellowship program directors (PDs) in 2019. Forty-eight (71.6%) of PCCM PDs responded. Our survey shows that PCCM fellows are not uniformly exposed to the same MV modalities, and PDs' perception of fellows' competency in managing MV is variable. Our results suggest that there is a lack of exposure to the various modes of “conventional” MV, as well as inconsistent education about less-utilized “nonconventional” MV. Additionally, we found that PDs are aware of their fellows' limited exposure to various modalities, as many practice patterns are institution specific. This study identified gaps in MV education and training and advocates for PCCM fellowship programs to identify these deficiencies to equip all trainees with a solid knowledge base that will prepare them to utilize any mode of MV in their future practice.
Keywords: pediatric; training; Pediatric Critical Care Medicine; PICU; fellowship; mechanical ventilation